Carrying capacity analysis of nature tourism at Selabintana, Gunung Gede Pangrango National Park, West Java - Andriyatno Sofiyudin; Rosadi Rosadi; Dolly Priatna (Universitas Pakuan, 2021)
Selabintana management area is one of the nature tourism areas in the Gunung Gede Pangrango National Park (GGPNP) which located in Sukabumi District, West Java. Within the management area which covers 2,547.93 ha, there is a camping ground and waterfall which both are the most attracted for visitors. Efforts are needed to harmonize nature tourism activities with conservation mission, so that visitors can enjoy but the natural environment is maintained. The objective of this research is to determine the carrying capacity for daily tourism and camping activities by considering the aspect of physical, environmental and management aspects. The survey conducted through interviews and questionnaires to 62 tourists, traders and managers of the national park area. The data were analyzed using the carrying capacity assessment method developed by Cifuentes, i.e. calculating the Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), and Effective Carrying Capacity (ECC). As a result, EEC for daily tourism is 84 visitors/day (PCC RCC ECC with a score of 3,269 98 84), while EEC for camping is 60 visitors/day (PCC RCC with a score of 2,155 69 60). Thus, carrying capacity of nature tourism activities in conservation areas can be calculated based on physical carrying capacity, real carrying capacity, and effective carrying capacity.Kawasan pengelolaan Selabintana merupakan salah satu areal wisata alam yang ada di Taman Nasional Gunung Gede Pangrango (TNGGP) yang terletak di Kabupaten Sukabumi, Jawa Barat. Di dalam areal pengelolaan yang luasnya 2.547,93 ha terdapat camping ground dan air terjun yang merupakan daya tarik utama yang bagi para pengunjung. Diperlukan adanya upaya untuk menyelarasakan kegiatan wisata alam dengan misi konservasi, agar pengunjung dapat menikmati namun lingkungan alam tetap terjaga. Tujuan dari penelitian ini adalah menentukan carrying capacity untuk kegiatan wisata harian dan berkemah dengan mempertimbangkan aspek fisik, lingkungan dan manajemen. Survey dilakukan melalui interview dan kuisioner terhadap 62 wisatawan, pedagang dan pengelola kawasan taman nasional. Data dianalisis dengan metode penilaian carrying capacity yang dikembangkan oleh Cifuentes, yaitu menghitung Daya Dukung Fisik (PCC), Daya Dukung Ril (RCC), serta Daya Dukung Efektif (ECC). Sebagai hasil, EEC untuk wisata harian adalah 84 pengunjung/hari (PCC RCC ECC dengan skor 3.269 98 84), sedangkan EEC untuk berkemah adalah 60 pengunjung/hari (PCC RCC dengan skor 2.155 69 60). Jadi, carrying capacity dalam kegiatan wisata alam di dalam kawasan konservasi dapat ditentukan berdasarkan daya dukung fisik, daya dukung riil, dan daya dukung efektif.